THE GUARANÍ MILITIAS IN THE JESUIT MISSIONS OF PARAGUAY AND RÍO DE LA PLATA: A CASE STUDY OF THE TRANSITION OF MILITARY ORGANIZATION AND TACTICS FROM EARLY MODERN SPAIN TO ITS OVERSEAS POSSESSIONS - Takeda, Kazuhisa (Revista de Historia Social y de las Mentalidades, 2017)
In the context of the military history of early  modern Spain, this article argues that the militia  organized by the Guaraní Indians under the  supervision of the Jesuits in the Río de la Plata  area, was intended for the purpose of tracing  the transference of military organization and  tactics from the Spanish monarchy to its overseas  colonies. The principal documents analyzed in  this article are a number of guidebooks having  reference to military theory and techniques,  published in Spain and other European  regions, and written orders of military exercise  transmitted by successive Jesuit superiors to the  indigenous peoples in the River Plate region.  The Spanish and Guaraní soldiers shared the  same mode of forming military units called  “Companies”, and in the battlefield they  organized a number of well-ordered military  formations called “Squadrons”
Keywords: Jesuit; Guaraní Indian; Military Organization; Company; Tercio; Squadron